PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PT INDOFARMA TBK PERIODE 2013-2022 - Sukmawati Putri, Intan; Nurwita (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of capital structure and profitability on the company value of PT Indofarma Tbk for the 2013-2022 period. Capital structure is measured by debt equity ratio (DER) and profitability by return on assets (ROA). Company value is assessed using price book value (PBV). The approach used is quantitative with secondary data obtained from company financial reports. The method used is multiple regression analysis. The research results show that DER and ROA do not have a significant influence on PBV, either partially or simultaneously, with an adjusted R square of 10%, indicating that 90% is influenced by other variables not studied.